PENGARUH CITRA SEKOLAH DAN PERSEPSI HARGA TERHADAP WORD OF MOUTH DAN KEPUTUSAN ORANG TUA MEMILIH SEKOLAH ANAK - Annisa Rahmawaty Arifin; Suwitho Suwitho; Djawoto Djawoto (Pascasarjana Universitas Halu Oleo, 2020)
This study discusses the direct influence of school image and price perception on word of mouth and the decision of parents to choose school children and the indirect effect of school image on parents' decision to choose school children through word of mouth as an intervening variable and the indirect effect of price perception on parents' decision to choose school children through word of mouth as an intervening variable. This research uses path analysis, F test, t test and sobel test. The sampling technique in this study is using the Slovin formula of 194 respondents from 3 school AL Azizi, Al-Amin and Aisyiyah schools in kelurahan Wage, kabupaten Sidoarjo. The results of this study indicate that the school's image has a positive and significant effect on the decision of parents to choose a child's school, the perception of price has a positive and significant effect on the decision of parents to choose a child's school, the school's image has a positive and significant effect on word of mouth, the price perception has a positive and significant effect on word of mouth, word of mouth has a positive and significant effect on the decision of parents to choose school children. In addition there is a significant mediating effect, word of mouth mediates the effect of the school's image on the decision to choose school and there is no mediating effect between the perception of price on the decision of parents to choose a child's school through word of mouth.